Effect of inertia on performance and fatigue pattern during repeated cycle sprints in males and females - Falgairette, G.; Billaut, F.; Giacomoni, M.; Ramdani, S.; Boyadijan, A. (International Journal of Sports Medicine, 2004)
The effect of recovery duration on performance and fatigue pattern during short exercises was studied including and excluding the flywheel inertia. Subjects (11 males and 11 females) performed a force-velocity test to determine their optimal force (fopt). On the following day, subjects performed randomly 4 series of two 8-s sprints against fopt, with 15 s (R15), 30 s (R30), 60 s (R60), and 120 s (R120) recovery between sprints. The cycle (Monark 824 E, Stockholm, Sweden) was equipped with an optical sensor to calculate the revolution velocity of the pedal. For each sprint, peak power (Ppeak), mechanical work (W) and time to reach Ppeak (tPpeak) were calculated including (I) and excluding (NI) the acceleration of the flywheel. For a given sprint, Ppeak and W were greater and tPpeak was lower in I compared to NI condition (p < 0.05). Differences averaged 13 % for Ppeak, 20 % for W, 34 % for tPpeak, and remained constant between sprints 1 and 2. In sprint 2, Ppeak and W were significantly reduced compared to sprint 1 only after R15 and R30 in I and NI (p < 0.05), and no gender differences occurred. In each sprint, Ppeak and W were higher (p < 0.001) and tPpeak was shorter (p < 0.05) in males than in females, and gender differences were the same including or excluding the flywheel inertia. In conclusion, values excluding inertia underestimated mechanical performance and consequently the total energy supply. However, the pattern of fatigue and gender differences in performance and fatigue remained unchanged whatever the condition (I or NI). This result may have practical implications when the flywheel inertia can not be taken into account in the calculation of mechanical work and power output.